Digital technology and rights in the lives of children with disabilities. (May 2017) - Alper, Meryl; Goggin, Gerard
Children with disabilities, especially those from the Global North, often figure into public discourse as beneficiaries of the "digital revolution." However, if children's voices and experiences are generally under-considered in digital policy and rights debates, this is even more likely when it comes to disability. Against this background, this article looks at the global rights of children with disabilities in the digital age. We consider the state of digital inclusion and exclusion, as well as the intersection between children's rights and disability rights. Moving forward, we suggest ways to reconceptualize digital and related rights inclusive of all children.